Stress pada Mahasiswa Keperawatan dan Strategi Koping yang Digunakan: Stress in Nursing Students and Coping Strategies Used - Yuni Aris; Rika Sarfika; Ira Erwina (NERS Jurnal Keperawatan, 2018)
The background: students in the first year lecture is the subject of that are vulnerable are subjected to stress. Response the stress not adequat and occurring in a long period of time can cause depression and even could lead to the action of suicide. Coping positive will lead to adaptation good. The purpose of this research is to find relations between the level of stress with strategy coping. Methods: sample in this research is a student nursing faculty nursing unand the first level and the level of class two english-language internasioanl (KBI), class a regular program are fulfilled, and the class regular program incongruous as much as a 122 people. Data collected with guide interview by using a questionnaire Perceived Stress Scale-14 (PSS-14) and questionnaires adolescent coping orientation for the problem of experiences ( acope). Measurements conducted simultaneously on student each class .In an analysis of data by using chi-square analysis. Results: the research results show as many as 63.7 % respectively students that experienced stress was on strategy coping that focuses on emotion , the rest of 36,3 % his use strategy coping focuses on the problem. Test results chi-square show there is meaningful relations between stress with strategy coping (Pv = 0,011 ). Conclusions: it is suggested that students capable of adapting to stresor by means of mensubstitusikannya into a challenges positive so the university students can remain productive without having to down to stress experienced.